2019
DOI: 10.1002/glia.23685
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide upregulates microglia phagocytosis and increases transient receptor potential vanilloid type 2 channel expression on the plasma membrane

Abstract: Microglia phagocytosis is critical for central nervous system development, and dysregulation of phagocytosis may contribute to a variety of neurological disorders. During initial stages of phagocytosis, microglia display increased nitric oxide (NO) production via inducible nitric oxide synthase (iNOS) activity and amplified calcium entry through transient receptor potential vanilloid type 2 (TRPV2) channels. The present study investigated the regulatory role of iNOS/NO signaling in microglial phagocytosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 63 publications
(110 reference statements)
0
25
0
Order By: Relevance
“…S1 A – C ) ( 21 , 22 ). Although TRPV2 was previously reported to be functionally expressed in microglia ( 23 ), its temperature threshold for activation exceeds the physiological range (>52 °C) ( 24 ). Thus, TRPV2 is likely not involved in temperature-dependent microglia movement, and we did not examine this channel further.…”
Section: Resultsmentioning
confidence: 99%
“…S1 A – C ) ( 21 , 22 ). Although TRPV2 was previously reported to be functionally expressed in microglia ( 23 ), its temperature threshold for activation exceeds the physiological range (>52 °C) ( 24 ). Thus, TRPV2 is likely not involved in temperature-dependent microglia movement, and we did not examine this channel further.…”
Section: Resultsmentioning
confidence: 99%
“…The specific recruitment of HDAC2 to NF- κ B at target promoters and the consequent effects on acetylation status may play an important role in regulating iNOS as well as other NF- κ B-dependent genes involved in inflammation [ 27 , 34 ]. Activation of microglia displays NO production via iNOS activity which upregulates microglial phagocytosis and increases TRPV2 expression [ 35 ]. Our experiment showed that CGRP increased the expression of iNOS, NF- κ B, and RIG-I protein levels in microglia after CGRP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO) is a free radical signaling molecule that regulates numerous physiological and pathological conditions. NO signaling has been shown to increase the expression of transient receptor potential vanilloid type 2, a calcium channel, and its trafficking to the plasma membrane via a PI3K dependent pathway (Maksoud et al, 2019), suggesting that NO signaling has the potential to regulate the expression of membrane proteins. Recently, differential regulatory effects of NO signaling on ASIC1a expression in the prefrontal cortex (PFC) and hippocampus have been confirmed.…”
Section: Chemicalsmentioning
confidence: 99%